Lead-Free Piezoelectrics. - Priya, Shashank (Springer, 2011)
Covering a key contemporary issue in the piezoelectrics ceramics industry, this volume is a comprehensive overview of current research into materials and products that contain alternatives to lead, the use of which is becoming ever more restricted.